Aggressive Behavior Towards Bullying In Early Adolescence - Budi, Heri Setyo; Budiman, M.Elyas Arif; Suswati, Wahyi Sholehah Erdah; Yuhbaba, Zidni Nuris (LPPM Universitas dr. Soebandi, 2025)
Introduction: Aggressive behavior is a destructive action that arises due to a lack of self-control. Aggressive behavior can result in negative interactions with peers, which has the potential to trigger bullying. The purpose of this study is to determine the relationship between aggressive behavior and bullying in early adolescents. Methods: This type of research is quantitative with a correlation design using a cross-sectional approach. The population is 163 students with a sample of 115 using the simple random sampling method. The research instruments used were questionnaires on aggressive behavior and bullying behavior. The data analysis in this study uses the Spearmen rank test. Results: The results of the study showed that 52.2% of aggressive behavior was at a moderate level and 40.9% of bullying was also at a moderate level. The results of the Rank Spearman test are known to have a p-value of 0.000 (≤ 0.05) and a correlation coefficient of 0.822, which means that there is a very strong relationship between aggressive behavior and bullying. Conclusions: Adolescents who exhibit aggressive behavior at moderate levels have the potential to engage in bullying behavior in certain situations. Adolescents need to be trained to recognize and manage emotions by providing education, counseling, and psychosocial support from schools through bullying prevention programs. Parents need to monitor adolescent behavior and become role models by implementing parenting that supports open communication so that adolescents can prevent the emergence of negative behaviors.